Stimulating Rural Growth and Economic Development through Rural Tourism in Bangladesh: A Study on Melandaha Upazilla in Jamalpur District - Islam, Nora (European Scientific Journal, ESJ, 2023)
Rural tourism development can ensure socio-economic development and environmental benefits to the people in any rural area. It contributes to society by creating business and job opportunities. It also guarantees rural residents a standard level of living by earning more. Bangladesh is a land of natural beauty. Melandaha Upazilla in Jamalpur District is a hidden treasure of natural beauties, enriched with colorful rural life, archeological and historical sites and cultural attractions. This destination can be a prominent rural tourism spot in Bangladesh by providing proper nurture. This article aims to recognize how rural tourism can be the best alternative of earning for rural people to minimize the dependency on seasonal work (e.g., agriculture, fishing, boating), create alternative sources of income, and ensure economic development as well as solvency through participation in rural tourism businesses. This study was undertaken to explore a secondary income source for rural people who depend on an agricultural-based economy. To test my assumption, I have conducted a survey questionnaire to identify whether the commencement of rural tourism can stimulate the economic growth of rural residents or not. This article identifies the major attractions and prospects of the rural tourism in this destination. Finally, this article also presents a SWOT analysis and suggests necessary recommendations for commencing rural tourism in Melandaha Upazilla.